Клинико-экономический анализ лечения хронического апикального периодонтита (LLC "Endo Press", 2020)
Today pharmaco-economic researches have become an integral part of demonstrative medicine. Clinical and economic researches of conservative treatment of chronic periodontitis was carried out using materials based on calcium hydroxide. The cost and efficiency analysis of conservative method of treatment is carried out using pastes kalsept, kalsept-iodine and metapeks.